2015
DOI: 10.5114/pg.2014.47501
|View full text |Cite
|
Sign up to set email alerts
|

13 CO 2 breath tests in non-invasive hepatological diagnosis

Abstract: In liver diagnostics, a simple, non-invasive test with high sensitivity and specificity is permanently being sought in order to assess the degree of liver damage. In addition to liver biopsy, algorithms using blood parameters or elastometry are used in clinical practice. However, these methods do not provide information about the true liver reserve, so the liver breath test seem to be a promising diagnostic tool. The basis of this test depends on the ability of particular hepatocyte enzyme systems to metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In addition, tumor stage may also affect the body's amino acid levels. It was reported that the concentration of tyrosine, methionine and phenylalanine in patients with hepatocellular carcinoma increased with tumor stage [25]. However, due to the small sample size of this study, we did not carry out the study of staging and amino acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, tumor stage may also affect the body's amino acid levels. It was reported that the concentration of tyrosine, methionine and phenylalanine in patients with hepatocellular carcinoma increased with tumor stage [25]. However, due to the small sample size of this study, we did not carry out the study of staging and amino acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the presence of steatosis, it is observed the shift of the peak metabolism rate from 10 minutes to 20-30-40-50 minutes of the test [3,6]. The progression of the pathological process leads to a decrease in the rate of metabolism and in the cumulative dose that characterizes the "capacity" of the liver [9]. However, for early diagnosis of NAFLD, it is important to evaluate the cumulative dose accumulation during the examination [3,9].…”
Section: Discussionmentioning
confidence: 99%
“…The progression of the pathological process leads to a decrease in the rate of metabolism and in the cumulative dose that characterizes the "capacity" of the liver [9]. However, for early diagnosis of NAFLD, it is important to evaluate the cumulative dose accumulation during the examination [3,9]. Thus, the points for difference between normal condition and pathology are metabolism levels of 1.05 at 10 minutes, 4.15 at 20 minutes, 7.15 at 30 minutes, 9.00 at 40 minutes, and 20.00 at 120 minutes [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation